Comorbid Anxiety and Depression and Related Factors Among Pregnant and Postpartum Chinese Women During the Coronavirus Disease 2019 Pandemic - Luo, Zheng; Xue, Luyao; Ma, Li; Liu, Zhengkui (Frontiers in Psychology, 2021)
Objective: To identify the prevalence of comorbid anxiety and depression (CAD) and analyze the relationship between CAD and sociodemographic and obstetric-related variables in pregnant and postpartum Chinese women during the COVID-19 pandemic. Methods: Participants were 2,237 pregnant and postpartum women (aged 19 – 47 years) recruited from medical institutions in China between February 28, 2020 and April 26, 2020. They were asked to complete an online survey assessing anxiety and depression, obstetric characteristics, and sociodemographic variables. The women were grouped into the following categories in accordance with the Generalized Anxiety Disorder Scale (GAD-7) and the Patient Health Questionnaire (PHQ-9): (a) comorbid anxiety and depression (CAD), (b) anxiety only, (c) depression only, and (d) no depression or anxiety. After estimating the prevalence of CAD, anxiety only, and depression only, we carried out chi-squared tests and multiple logistic regression to examine related factors between these groups of pregnant and postpartum Chinese women. Results: CAD, anxiety only, and depression only occurred in 6.3%, 5.8%, and 3.9% of participants, respectively. The prevalence rates of CAD during the first, second, and third trimesters of pregnancy and the postpartum period were 7.4%, 6.5%, 5.7%, and 8.2%, respectively. The factors that differed among the groups were age (p < 0.05), marital status (p < 0.001), level of education (p < 0.05), family support (p < 0.001), and total live births (p < 0.001). “Poor family support” (OR: 1.90; 95% CI: 1.30 - 2.78; p = 0.0009) and “no birth” (OR: 1.91; 95% CI: 1.32 - 2.75; p = 0.0006) remained significant factors for the CAD group, while “poor family support” (OR: 2.16; 95% CI: 1.34 – 3.47; p = 0.0015) remained a significant factor for the “depression only” group, when their results were compared to those of the “no depression or anxiety” group in the multiple logistic regression analysis. Conclusion: Pregnant and postpartum Chinese women with poor family support and primipara are at a high risk for CAD during the COVID-19 pandemic. These results support the need for targeted perinatal programs to address CAD in pregnant and postpartum women during the pandemic period.